Distribusi Syzygium cumini (L) Skeels di Aceh Besar - Afridah Afridah Rosannah; Nursahara Pasaribu; Saleha Hannum (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
The jamblang distribution has been studied in the southern part of Aceh Besara, which is in the South of Jhanto district, Northern Krueng Raya, Southern Masjid Raya and Ujung Pancu district. The aims ofthis study was to determine the distribution area of jamblang based on rainfall, soil type, and lands cover . The data were collectedby observation. Distribution data are presented in the form of map using ArcView 3.3 Software. The results of the analysis showed that the common jamblang was distributedin the rainfall region of 1500-2500 mm/year in dryland farming and the chromic luvisols, humic acricols, dystric fluvisols, dan rendzinas.